Potensi dan Karakterisasi Fisiologis Bakteri Endofit Asal Tanaman Kakao Sehat sebagai Pemacu Pertumbuhan Benih Kakao - Andi Khaeruni; Tanza Nirmala; Waode Siti Anima Hisein; Gusnawaty Gusnawaty; Teguh Wijayanto; Gusti Ayu Kade Sutariati (Institut Pertanian Bogor, 2020)
This study aimed to obtain endophytic bacterial isolates originated from healthy cacao plant, potential for plant-growth promoting of cacao seedlings. This study was carried out in the Phytopathology Laboratory Unit of the Plant Protection Department, Faculty of Agriculture, Halu Oleo University. This study was conducted using a completely randomized design (CRD) using ten isolates of endophytic bacteria from healthy cocoa plants as treatments, plus a control treatment. The experiment was conducted in a screenhouse using seed treatment and planted in seedling boxes, containing sterile rice-husk charcoal as a growing medium. The result showed that three endophytic bacteria tested (isolates 2RPR1, 2RWB2, and 5BRB3) were potential as plant growth-promoting of cocoa seedlings, because the isolates were able to increase seed germination up to 96.67%, relative growth rate up to 90-96.67%, increased plant height up to 47.85-67.17%, root dry weight up to 35.08-52.63%, and canopy dry weight up to 97.71-108.46%. The superiority of the three isolates were related to their abilities to fix nitrogen, dissolve phosphate, as well as to produce indole acetic acid. Keywords: cacao, endophytic bacteria, plant growth-promoting agent, seed viability